Vartotojų empatinis atsakas ir emocinis įsitraukimas į Lietuvos Raudonojo Kryžiaus socialinę reklamą - Kryževičiūtė, Karolina (Vilnius University Open Series, 2025)
Social advertising’s orientation towards solving social problems demonstrates the exeptional importance of consumers engagement. One of dimension of consumers engagement, emotional engagement, reveals the relevence of research on consumers’s emotion ant the emnphatic responce, evoked by advertising. The relevance of this research is also supported by observation of researchers that social advertisements are characterised by an abundance of emotional appeals.The aim of the present study is to investigate the emotions and emphatic response evoked in consumers of social advertisemens of Lithuanian Red Cross, as well as the impact on the emotional engagement of these consumers in social advertisement of different emotional valence. The study evaluated the emotional valence of the selected social advertisings apeals ,,Overiew“ software, wich using artificial intelligence algorithms for facial and voice emotion recognition. During the experiment, these advertisements were shown to research participants, whose emotion durring the processing of these advertisenment were identified by ,,Overview“. During the experiment, the participants were interviewed to determine the emotion, they perceived thenselves to be experiencing and to determine their emphatic response and emotional engagement.The study showed, that emotionally valet appels in social advertising evoke consumers emotions. The creativity of the advertisement may have an importance on the consumers’ emotions. The most intense emotion experienced by the participants of research, according to ,,Overview”, was sadness. However, while emotional appeals with different valence in social advertising elicit an emphatic consumers response, neutral appeals do not. The study shows a trend, that emphatic response is directly related to consumeras’ emotional engagement with social advertisement.
Keywords: socialinė reklama; reklamos kreipinių emocinis valentingumas; emocinė vartotojų reakcija; empatinis atsakas; emocinis vartotojų įsitraukimas